The Impact of Vitamin D on The Development of Multiple Sclerosis (Review article) - Aseel Ghassan Daoud; Huda Jaber Waheed; Mayssaa Essam Abdala (College of Pharmacy / Mustansiriyah University, 2022)
Multiple Sclerosis is a harmful disease causes severe and painful symptoms. In the recent period, researchers have tended to study the effect of vitamin D deficiency on general health. Several studies have reported that there is a relation between vitamin D levels and MS disease progression. Epidemiological testimony and reports have recorded that there are an association between the decrement in plasma vitamin D levels and the incidence of MS also with the disease development; and it has seen that when take vitamin D as supplement may protect the MS patients against disease development. Despite clear evidence of the correlation between disease progression and vitamin D deficiency but the mechanism yet unclear.